Penggunaan Metode Pembelajaran Inovatif dan Hubungannya dengan Kemampuan Mengoptimalkan Gaya Belajar Siswa - Fatimah Ahmad; Khairuddin Khairuddin; Usria Agus Tila (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
This study aims to determine the effect of Innovative learning methods on learning styles in Aqidah Akhlak lessons for eighth grade students of MTs Darul Arafah Pangkalan Berandan. This research method uses quantitative data analyzed using descriptive statistics and inferential statistics. Innovative learning is learning that provides more opportunities for students to construct knowledge independently and mediated by peers. Based on the results of research and data analysis, it can be concluded that the Innovative learning method at MTs Darul Arafah Pangkalan Berandan has an average result of 36.33, a median of 36.5, a mode of 37, a variance of 24.95 and a standard deviation of 4.99. acceptable with a significant limit of tolerance. Learning Styles of students at MTs Darul Arafah Pangkalan Berandan have an average result of 47.9, a median of 48.5, a mode of 47.6, a variance of 9.40 and a standard deviation of 3.06. acceptable with a significant limit of tolerance. There is a significant effect between Innovative learning methods in improving the learning styles of students at MTs Darul Arafah Pangkalan Andan with the results Fcount = 31.15 and Ftable (1.28) (0.01) = 7.56 which can be concluded Fcount≥Ftable by accepting Ha and rejecting H0 with a regression line equation of (Y= ) 45.57+0.06X.